(untitled) (Revista Sistemas de Producción Agroecológicos, 2024)
Renewable biofuels have several advantages, including increasing energy efficiency, diversifying the energy matrix of countries, and reducing greenhouse gases. Moreover, fossil fuels are gradually depleting. Biofuels such as biodiesel and renewable diesel, also known as green diesel or hydrotreated vegetable oil, are becoming essential fields of study as they can mitigate environmental damage without affecting transportation quality. Both biodiesel and renewable diesel are produced from the same biomass, which can come from vegetable oil, animal fats, microalgal oil, or waste cooking oil. Each fuel is created through a different process, transesterification for biodiesel and hydrotreatment for renewable diesel. As a result, each has distinct chemical and physical properties that determine their performance, including efficiency and CO2 emissions. This review examines the biomass feedstock used, compares the transformation processes, efficiency, and potential CO2 emissions, and identifies the advantages and disadvantages of using biodiesel and renewable diesel.